REFLECTION ON CLASSROOM TEACHING OF PROBABILITY AND MATHEMATICAL STATISTICS - Meng Tian, (IJRDO -JOURNAL OF MATHEMATICS, 2019)
This paper focuses on the class teaching of probability theory and mathematical statistics course. It points out the problems exists in current teaching classes and puts forward some teaching suggestion to stimulate students’ interest in probability theory and mathematical statistics. The use of knowledge of Probability Theory and Mathematical Statistics can help students solve practical problems.